CRIMINAL LIABILITY FOR MISUSE OF ARTIFICIAL INTELLIGENCE TECHNOLOGY (ARTIFICIAL INTELLIGENCE/AI) IN THE PERSPECTIVE OF THE NATIONAL CRIMINAL CODE - Agus Siagian; Erniyanti; Irpan Husein; Markus Gunawan (PT. Radja Intercontinental Publishing, 2026)
The development of Artificial Intelligence (AI) technology has provided significant benefits across various sectors; however, it has also led to various forms of misuse, including deepfakes, digital fraud, data manipulation, and cybercrime. The regulation of criminal liability for AI misuse in Indonesia is currently based on the Indonesian Criminal Code (KUHP), Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 on Electronic Information and Transactions, as well as other relevant laws and regulations. Its implementation still faces several challenges, including the absence of specific legal provisions, difficulties in digital evidence, and the determination of the responsible legal subject. Therefore, strengthening legal regulations and developing adaptive criminal law policies are essential. This study aims to analyze the legal framework, implementation, challenges, and solutions concerning criminal liability for the misuse of Artificial Intelligence from the perspective of the Indonesian Criminal Code. This study employs the theories of Criminal Liability, Legal Certainty, and Law Enforcement as the analytical framework. The conceptual framework encompasses criminal liability, the misuse of Artificial Intelligence, and the Indonesian Criminal Code. This research applies a normative legal research method using statutory, conceptual, and case approaches. The study relies on secondary data consisting of primary, secondary, and tertiary legal materials, which are analyzed qualitatively. The findings indicate that the current legal framework governing criminal liability for AI misuse has not yet provided adequate legal certainty, resulting in challenges related to evidence and the determination of responsible parties. The novelty of this research lies in the development of a criminal liability concept that integrates the principles of fault, accountability of AI developers, providers, and users as part of the reform of Indonesia’s national criminal law. This study concludes that the regulation of criminal liability for the misuse of Artificial Intelligence should be strengthened to accommodate technological advancements while ensuring legal certainty. It recommends the enactment of specific AI regulations, harmonization with the Indonesian Criminal Code, and the enhancement of law enforcement capacity in addressing AI-related crimes.